Enamoured with Piety: Godliness as the Pervading Theme in the Thought and Ministry of Thomas Watson (c. 1620–1686), by Yarran Johnston - Payne, Matthew N. (The Evangelical quarterly, 2021)
"Enamoured with Piety: Godliness as the Pervading Theme in the Thought and Ministry of Thomas Watson (c. 1620-1686), by Yarran Johnston" published on 09 Nov 2021 by Brill.